Industry 4.0: The Challenge on the Road to Digital Organizations - Mora-Sánchez, Dorian (2020)
The fourth industrial revolution, known as Industry 4.0, encourages industrial physical systems to be connected to the digital world, forcing organizations out of their Status Quo. This reality represents a precedent for organizations to conceive this new revolution in order to migrate to this paradigm from where they currently are. The main objective of this article is to know the challenges that the fourth industrial revolution brings for organizations, by externalizing its importance and characteristics, and explaining its influence on aspects related to its implementation in organizations. The exploratory methodology used includes a literature review in the most important scientific databases on specific aspects such as: industrial revolutions, characteristic features of Industry 4.0, and its influence on organizations. The results can show the influence of the different industrial revolutions, the intrinsic details of Industry 4.0, the attention that its implementationmay require within organizations, and open up the possibility of having a sustainable 4.0 organization approach. Finally, it is concluded that in order to migrate to Industry 4.0, an organization must understand the challenges in managing its operations, human talent, energy, operations, strategy, and sustainability.